Trail log - 2015 - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2015)
May, Wuhan, China, Conference, Chinese Environmental Ethics, and trip to Three Gorges Dam. June, Pomona, California, Conference "Seizing an Alternative: Toward an Ecological Civilization," Claremont colleges, John Cobb, Bill McKibben, Vandana Shiva, Wes Jackson. June, Bahamas, Nassau, Templeton Foundation Meeting, and Powerboat Adventure, trip to Allen's Cay and Ship Channel Cay. July, trip to Kiel Germany, and International Society for Environmental Ethics, meeting at Christian-Albrechts-Universitët. Field trips to Dasenmoor, peat bog, and Wadden Sea, intertidal zone, tidal flats and wetlands. October, trip to Virginia to speak at Westminster Canterbury Richmond and to Shenandoah National Park and Shenandoah Valley. Local hikes and trips.